FINDING THE LEVEL OF PROFESSIONAL-PEDAGOGICAL PREPARATION OF STUDENTS AS A PEDAGOGICAL PROBLEM - Sh.M. Khudaykulova (Zeta Repository, 2023)
In the article, the composition of the level of professional-pedagogical preparation of students is studied as a pedagogical problem. qualitative indicators of qualimetry are studied by dividing them into natural and social indicators.